2008
DOI: 10.1080/14756360701632031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AChE by malathion and some structurally similar compounds

Abstract: Inhibition of bovine erythrocyte acetylcholinesterase (free and immobilized on controlled pore glass) by separate and simultaneous exposure to malathion and malathion transformation products which are generally formed during storage or through natural or photochemical degradation was investigated. Increasing concentrations of malathion, its oxidation product malaoxon, and its isomerisation product isomalathion inhibited free and immobilized AChE in a concentration-dependent manner. K I , the dissociation const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 33 publications
4
15
0
9
Order By: Relevance
“…Neostigmine resulted in two IC 50 values, 50 Ϯ 25 M and 38 Ϯ 10 nM, based on two-site competition fitting. These numbers generally agreed well with previously reported values (eserine 72-109 nM [34], malathion 370 M [35], edrophonium 5.4 M [36], and neostigmine 11.3 nM [37]; however, direct comparison of these numbers might not be appropriate because the experimental conditions were not identical (e.g., use of surrogate substrates and different AchE in other assays).…”
Section: Ache Inhibitor Characterizationsupporting
confidence: 81%
“…Neostigmine resulted in two IC 50 values, 50 Ϯ 25 M and 38 Ϯ 10 nM, based on two-site competition fitting. These numbers generally agreed well with previously reported values (eserine 72-109 nM [34], malathion 370 M [35], edrophonium 5.4 M [36], and neostigmine 11.3 nM [37]; however, direct comparison of these numbers might not be appropriate because the experimental conditions were not identical (e.g., use of surrogate substrates and different AchE in other assays).…”
Section: Ache Inhibitor Characterizationsupporting
confidence: 81%
“…OP degradation processes also occur in chemical treatments for purification of polluted waters, generally referred as advanced oxidation processes, as well as throughout the enzymatic reactions in birds, fish, insects and mammals. Degradation studies revealed different kinetics, mechanisms and transformation products, suggesting complete mineralization of the starting compound (usually thio form), but forming toxic break down products as well [89, 97-100]. Actually, oxidation and isomerisation reaction products were reported as much more potent AChE inhibitors compared to the starting thio OPs, while hydrolysis products do not noticeably affect the enzyme activity.…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…Malathion is a broad-spectrum insecticide and chosen as a model compound, because it has been one of the most commonly applied OPs since 1956 [34]. Hence, in the present work it was chosen as standard pesticide for the AChE inhibition.…”
Section: Inhibition Measurementmentioning
confidence: 99%